Louise Erdrich's The Round House: Restorative Justice in a Coming of Age Thriller - Castor, Laura Virginia (Nordlit, 2018)
In a novel critics have described as a "thriller-like" coming-of-age story, Louise Erdrich's The Round House (2012) integrates two apparently conflicting approaches to Native American law. First, Felix S. Cohen's Handbook of Federal Indian Law legitimizes the need for working with allies to Indigenous peoples in developing contextual applications of settler state laws. The second draws on the authority of authorless Anishinaabe stories and dreams. While Cohen and his descendants in tribal law practice are allies to the Anishinabeg, dream narrations by the narrator's grandfather affirm the contemporary vitality of Anishinaabe approaches to justice. Finally, Erdrich's narration suggests why restorative justice for women in Indigenous communities in the United States should matter for her international audience.